Institutional Change and Performance Analysis of Local Government-Owned Water Supply Companies in West Java, Indonesia - Alizar, Anwar (2024)
Indonesia's city water supply companies (PDAMs) were facing challenges in achieving 100% coverage by 2024, a target set by the government. It was primarily due to institutional challenges within and between these entities. The government intervention in enhancing PDAM performance was not effective, because it was not driven by professional justifications. Despite government technical support, such as rehabilitating non-functional water systems, capacity building, and providing grants, these efforts have not significantly improved PDAMs' performance. This study investigated the influence of institutional changes on performance improvement in the (PDAMs). It examined multiple dimensions that affect the company's performance, including service provision, financial administration, technological procedures, and human resources development. The study included a review of the performance of PDAMs throughout Indonesia and by conducting a more in-depth study of PDAM Depok. Specifically, the performance of the 11 PDAMs participating in the NUWSP project was also studied, particularly in the completeness of the standard operating procedures that each PDAM had. The essential feature of this study method was that the researcher has been involved deeply in the technical assistance and capacity building of the PDAMs that participated in the project. The basic findings of this research were that PDAMs faced the challenges of maintaining and improving their services while addressing the needs of their customers, regulators, the environment, acquiring technologies, and institutional changes. Problems related to the performance of PDAMs always recur from time to time, and this recurring problem was the main challenge faced by the PDAMs. The recurring problems related to institutions that affected PDAM performance were related to institutional aspects, including regulative, normative, and cultural-cognitive. The recurring performance problems at the national level included low tariffs, PDAM financial management that tended not to improve, water quality, non-revenue water, and human resources development. This study found that the recurring problems of PDAM performance were caused by a combination of factors related to company performance institutional aspects, resource constraints, and lack of political will. The study also concluded that to strengthen performance, third- party involvement that is strong in operational issues is needed to enforce efficiency.